Working Group Report on Health Financing and Management for the Eighth Five Year Plan (1990-95) - Planning Commission (Planning Commission Government of India, 1989)
The Working Group on Health Financing and Management, constituted by the Planning Commission in May 1989, examined the critical challenges in health service delivery and financing for India’s Eighth Five-Year Plan (1990–95). The report highlights systemic inefficiencies in health management, including underutilized resources, high administrative costs, and ad-hoc planning, particularly at primary and district levels. Key recommendations focus on strengthening management through the establishment of a specialized Health Management Cadre, enhanced training programs, and improved leadership in health institutions. On financing, the report emphasizes the need for increased government allocations, development of community-level financing mechanisms, expansion of health insurance coverage, and strategic public-private partnerships to improve access and quality. Additionally, the report underscores the importance of health services research for cost-effectiveness and delivery system optimization. By integrating management reform with equitable financing strategies, the Working Group provides a comprehensive framework aimed at achieving “Health for All by 2000,” ensuring efficient resource use, community participation, and sustainable healthcare development.
Government of India Planning Commission New Delhi May, 1989
Keywords: Health Management; Health Financing; Eighth Five-Year Plan; Resource Mobilization; Health Services; Managerial Cadre; Training and Education; Public-Private Partnerships; Community Financing; Health Insurance; Equity in Healthcare; Health Policy